AED Withdrawal in Children with Cerebral Palsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
The safety of antiepileptic drug (AED) withdrawal in 65 children with cerebral palsy (CP) who had been seizure-free for at least 2 years was investigated in the Neurology Department, Texas Scottish Rite Hospital for Children, Dallas.